2010
DOI: 10.1159/000320868
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Physical Training Attenuates the Effects of Perinatal Undernutrition on the Morphometry of the Splenic Lymphoid Follicles in Endotoxemic Adult Rats

Abstract: Background/Aims: Physical training is a well-known inducer of positive physiological adaptations. The effects of moderate physical training on the morphometry of splenic lymphoid follicles of endotoxemic rats submitted to a perinatal low-protein (LP) diet were evaluated. Methods: Male Wistar rats were divided into two groups according to their mother’s diet (17% casein, control, C) and, undernourished (8% casein, LP diet). On postnatal day 63, the animals were submitted to moderate physical training (8 weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 53 publications
4
15
1
Order By: Relevance
“…Moreover, protein restriction at this time may negatively affect the establishment of clonal diversity and the homeostasis of lymphocytes [11]. Consistent with previous finding, our results showed that perinatal low-protein diet is related to a reduced percentage of blood B lymphocyte, high percentage of spleen NK lymphocytes, and no changes in the percentage of differential TCD3+ lymphocytes in the peripheral blood [7,13,40]. However, to study the dynamic, morphology, and the differential count of circulating lymphocytes, it is necessary to submit Fig.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, protein restriction at this time may negatively affect the establishment of clonal diversity and the homeostasis of lymphocytes [11]. Consistent with previous finding, our results showed that perinatal low-protein diet is related to a reduced percentage of blood B lymphocyte, high percentage of spleen NK lymphocytes, and no changes in the percentage of differential TCD3+ lymphocytes in the peripheral blood [7,13,40]. However, to study the dynamic, morphology, and the differential count of circulating lymphocytes, it is necessary to submit Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that early low-protein diet is associated with alterations in the percentage of blood and splenic lymphocytes and loss of lymphoid cells in the spleen by enhanced apoptosis rate. Regardless of the period of the recovery, maternal low-protein diet largely affected the spleen as described in previous study [13]. However, these effects seems to be reversible, and we tested the hypothesis that moderate physical training attenuates the long-term effects of a perinatal low-protein diet on the process of immune defense by maintaining the percentage of Fig.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations